Kunhu Kaaryangalute Otethamburaan - Arundhati Roy; Priya, A S (Kottayam D C Books, 2011)
Translation of 'God of small things', the winner of Booker prize 1997.Set mainly in Kerala, India, in 1969, The God of Small Things is the story of Rahel and her twin brother Estha, who learn that their whole world can change in a single day, that love and life can be lost in a moment. Armed only with the invincible innocence of children, they seek to craft a childhood for themselves amid the wreckage that constitutes their family.
Keywords: ENGLISH NOVEL-MALAYALAM TRANSLATION; INDIAN ENGLISH NOVEL